When is a Question a Question for Children and Adults?. Issue 3 (3rd July 2017) - Saindon, Mathieu R.; Trehub, Sandra E.; Schellenberg, E. Glenn; van Lieshout, Pascal H. H. M.
ABSTRACT: Terminal changes in fundamental frequency provide the most salient acoustic cues to declarative questions, but adults sometimes identify such questions from pre-terminal cues. In the present study, adults and 7- to 10-year-old children judged a single speaker's adult- and child-directed utterances as questions or statements in a gating task with word-length increments. Listeners of all ages successfully used pre-terminal cues to identify utterance type, often only the initial word, and they were more accurate for child-directed than adult-directed utterances. There were age-related differences in identification accuracy and number of words required for correct identification. Age differences were already apparent on the initial (first five) utterances, confirming adults' superior explicit knowledge of intonation patterns that signify questions and statements. Adults' performance improved over the course of the test session, reflecting taker-specific learning, but children exhibited no such learning.